Theoretical Study on Nonreciprocity for Third-Harmonic Generation Process in Nonlinear Photonic Crystals - Dongrui Di; Binglin Zhang; Jiaying Wang; Ronger Lu (IEEE Photonics Journal, 2023)
Based on the nonlinear coupled wave equations, the nonreciprocal response of the third-harmonic generation process has been theoretically investigated in nonlinear photonic crystals with a defect embedded. The simulation results have shown that complete nonreciprocity for third-harmonic generation can be achieved under specific conditions, and the arbitrary nonreciprocal response can be realized by adjusting the structure parameters, including the crystal length, the defect position and the defect width. These findings hold great potential for implementing practical nonlinear optical isolating devices.